Corporate Value of ASEAN-2 Banks: The Impact of Risk Management and Corporate Governance - Wildan, Wildan; Maulana, Tubagus Rama; Kuswardhana, Trias; Leon, Farah Margaretha (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2024)
The dimension of the audit committee influences effective corporate management and can control risks arising from uncertainty, playing a vital role in enhancing a company's value. This research aims to examine the impact of Corporate Governance and Risk Management on the value of banking companies in two ASEAN countries, namely Indonesia and Malaysia, by collecting data from 41 Indonesian banks and 10 banks in Malaysia using a purposive sampling method, as well as utilizing secondary data from both the Indonesia Stock Exchange and the Malaysian Stock Exchange spanning 2019 through 2022. Data processing involved multiple regression analysis and Eviews 9. The research findings indicate that the size of LNBDSIZE and AGE has a positive impact, BDINDEP, BLAU, OWNC, ACS, and LNSIZE have no significant effect, while LVG has a negative impact. This study benefits financial managers in understanding the factors influencing the value of companies in the banking industry, namely Corporate Governance and Risk Management. Investors can gain insights into the factors affecting company valuation and identify potential risks as a basis for selecting investments in companies with sound financial ratios and risk management.